Second national development plan, 1970-74 : programme of post-war reconstruction and development - Federal Republic of Nigeria (Lagos : Federal Govt. Printer, 1970)
This book contains the policy frame work for, and the programme for the reconstruction of the war damaged areas and the construction of the rest of the country.
Call number of original: HC517.N48A495.
oo 29/08/2018
Loans
Keywords: Economic policy; Economic planning; Nigeria